Materialities of legal proceedings = Materialitäten der Gerichtsverhandlung - Scheffer, Thomas (2004)
The author explores materialities as pre-established and co-producing features of criminal proceedings. This is done by discussing courtrooms, files and stories in relation to English Crown Court hearings. The three materialities gain significance in the course of the court hearing, but do not derive from it. They exceed the course of talk-in-court. Once the hearing started, the pre-established materialities can be referred to but not simply modified. Materialities, in this line, provide stability and guidance for the hearing. They facilitate, purify and condense it. However, their temporal separation causes problems for those who run the show. Materialities can be employed but not fully integrated. Unwelcome parts do, at times, disturb, disrupt and complicate the current dealings.